Legal Regulation of The Civil Liability of The Air Carrier for Damages to The Goods - Amera Jaafar Shareef; Bakhshan Rashid Saeed; Hawre Nuraddin Sabir (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
The main focus of this research will revolve around the topic of damage to goods during air transport operations (aviation accidents, delay and cancellation of flights, poor level of services) as it deals with the legal basis for the liability of the air carrier for damage to goods and compensation for the damages caused under the international laws and agreements, especially in light of the increase in the percentage of aviation accidents and the aggravation of damages that has resulted in a low level of confidence and protection of consumers rights. The research will further emphasis on the nature of air carrier, the scope of air transport contract, the elements of the responsibility of the air carrier, the liability claim, the position of Iraqi laws and regulation in comparison with the international agreements on the responsibility of the air carrier for damage to goods. The research reached several results, the most important finding is on the basis of the responsibility of the carrier found in the Warsaw Convention which highlights the fault of the air carrier, but the fault can be proven otherwise under the international agreements, especially the Warsaw Agreement adopted by comparative laws, have been self-regulating when dealing with provisions for passenger transport by air, despite this and as a result of the bifurcation of air transport operations. This agreement failed to take into account the regulation of all the rights granted to passengers as a result of the air transport process and the damages that they suffer as a result of that process. The research recommendations are primarily initiated on the responsibility of the air carrier where the foundation lays on bearing dependency and that the responsibility of the air carrier should be based on the liability and the obligation to provide compensation. Furthermore, the legislator has to distinguish between the responsibility of the carrier for the personal injuries caused to the passengers and the goods more precisely, and to encourage air transport companies with a decent financial position to invest in this field, and operate on the basis to provide full compensation for moral damages in addition to the material damage and to offer full clarification in this regard.